DEVELOPING TEACHING MEDIA POWTOON FOR WRITING DESCRIPTIVE TEXT AT GRADE 8 STUDENTS OF SMPN 6 PERCUT SEI TUAN - Dio Ilham Prasetyo Siregar; Rika Rika (Universitas Negeri Medan, 2021)
The objective of this study is to develop PowToon as media for teaching the 8 studentsin writing descriptive text at SMPN 6 Percut Sei Tuan. This study used the qualitativedescriptive method. This research was conducted based on educational research anddevelopment (R&D) through six steps, namely: gathering data, analyzing data,designing media, validating by the expert, revising media, and final product. TheInstrument of Collecting Data was questionnaire. The finding showed that one videoof PowToon was used to teach English writing to Junior High School. The developedmedia PowToon had been validated by two experts and the average score has gottenwas 87%. It was categorized “Excellent” since that the developed to teaching mediaPowToon for writing skills were suitable for the 8 grade students of SMPN 6 PercutSei Tuan.